Contemporary Methods for Graph Coloring as an Example of Discrete Optimization - Adrian Bilski (International Journal of Electronics and Telecommunications, 2019)
The following paper provides an insight into application of the contemporary heuristic methods to graph coloring problem. Variety of algorithmic solutions for the Graph Coloring Problem (GCP) are discussed and recommendations for their implementation provided. The GCP is the NP-hard problem, aiming at finding the minimum number of colors for vertices in such a way that none of two adjacent vertices are marked with the same color. With the advent of modern processing units metaheuristic approaches to solve GCP were extended to discrete optimization here. To explain the phenomenon of these methods, a thorough survey of AI-based algorithms for GCP is provided, with the main differences between specific techniques pointed out.